The Effect of Guided Discovery Learning Model towards the Mathematics’ Critical Thinking Ability on Secondary School Students - Samron, Samron; Arua, Afudin La (Universitas Negeri Surabaya, 2021)
This study is aimed to determine the effect of guided discovery learning model on mathematical thinking ability of secondary school students. This study was a quasi-experimental study involving students in the VIII grade at SMP Negeri 9 Baubau, Southeast Sulawesi Province. T-test analysis is used to analyze the collected data. The findings revealed that (1) the guided discovery learning model had a significantly better on improving students. Mathematical critical thinking skills than the direct learning model; (2) both classes experienced an increase in every aspect of mathematical critical thinking skills, but the the guided inquiry learning model had asignificantly higher increase in every aspect of mathematical critical thinking skills than the direct learning model.